Identification and control of subglacial water networks under Dome A, Antarctica. Issue 1 (24th April 2013) - Wolovick, Michael J.; Bell, Robin E.; Creyts, Timothy T.; Frearson, Nicholas
Abstract : [1] Subglacial water in continental Antarctica forms by melting of basal ice due to geothermal or frictional heating. Subglacial networks transport the water from melting areas and can facilitate sliding by the ice sheet over its bed. Subglacial water flow is driven mainly by gradients in overburden pressure and bed elevation. We identify small (median 850 m) water bodies within the Gamburtsev Subglacial Mountains in East Antarctica organized into long (20–103 km) coherent drainage networks using a dense (5 km) grid of airborne radar data. The individual water bodies are smaller on average than the water bodies contained in existing inventories of Antarctic subglacial water and most are smaller than the mean ice thickness of 2.5 km, reflecting a focusing of basal water by rugged topography. The water system in the Gamburtsev Subglacial Mountains reoccupies a system of alpine overdeepenings created by valley glaciers in the early growth phase of the East Antarctic Ice Sheet. The networks follow valley floors either uphill or downhill depending on the gradient of the ice sheet surface. In cases where the networks follow valley floors uphill they terminate in or near plumes of freeze‐on ice, indicating source to sink transport within the basal hydrologic system. Because the ice surface determines drainage direction within the bed‐constrained network, the system is bed‐routed but surface‐directed. Along‐flow variability in the structure of the freeze‐on plumes suggests variability in the networks on long (10s of ka) timescales, possibly indicating changes in the basal thermal state. Key Points: We have used radar to image small subglacial water bodies The water bodies are organized into large networks The networks reoccupy a valley system that predates the ice sheet